2011
DOI: 10.1073/pnas.1009908108
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal influenza infection and live vaccine prime for a response to the 2009 pandemic H1N1 vaccine

Abstract: The robust immune response to a single dose of pandemic 2009 H1N1 vaccine suggests that a large segment of the population has been previously primed. We evaluated the effect of seasonal (s) H1N1 infection, s-trivalent inactivated vaccine (s-TIV), and trivalent s-live attenuated influenza vaccine (s-LAIV) before immunization with a pandemic live attenuated influenza vaccine (p-LAIV) in mice. We compared serum and mucosal antibody and pulmonary CD8 and CD4 responses and the virologic response to challenge with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
46
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(48 citation statements)
references
References 44 publications
(52 reference statements)
2
46
0
Order By: Relevance
“…Depending on the study and region analyzed, individuals under the age of 25 years represented 45% to 60% of infected subjects, though the pathogenic effects of H1N1 virus infection were most pronounced in individuals more than 60 years old (4,36). These findings, as well as recent immunological studies from our laboratory and other laboratories (11,17,20,22,25,33,39,48,51,52,55,61,62), suggest that previous encounters with vaccines or viruses provide immunological advantages and immunological memory in the population despite the "serological distance" between the hemagglutinin (HA) and neuraminidase (NA) proteins of seasonal and pandemic strains.…”
supporting
confidence: 64%
“…Depending on the study and region analyzed, individuals under the age of 25 years represented 45% to 60% of infected subjects, though the pathogenic effects of H1N1 virus infection were most pronounced in individuals more than 60 years old (4,36). These findings, as well as recent immunological studies from our laboratory and other laboratories (11,17,20,22,25,33,39,48,51,52,55,61,62), suggest that previous encounters with vaccines or viruses provide immunological advantages and immunological memory in the population despite the "serological distance" between the hemagglutinin (HA) and neuraminidase (NA) proteins of seasonal and pandemic strains.…”
supporting
confidence: 64%
“…We have previously shown that antibodies elicited by vaccination of adults with the inactivated seasonal influenza vaccine are not reactive with the LAH component of the HA stalk (21); in contrast, we show here that pH1N1 infection does elicit LAH-specific serum antibody. This finding may be a result of enhanced antistalk titer generated specifically by infection with the pandemic virus that expressed an antigenically different globular head, or it could be related to the observation that infection/vaccination with live-attenuated strains results in distinct and broader patterns of immunity compared with exposure to inactivated influenza antigens (24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 96%
“…However, when clinical trials of the inactivated 2009 H1N1pdm vaccine were undertaken, a single dose of vaccine was sufficient in all except children younger than 3 years of age, indicating that most of the population had been primed by prior exposure or vaccination with seasonal H1N1 viruses. We evaluated this phenomenon in a mouse model and demonstrated that priming was achieved by infection with seasonal H1N1 influenza virus or seasonal LAIV but not by seasonal inactivated influenza vaccine (47). In the present study, we evaluated sera from 56 subjects from three age groups, 18 to 32 years old, 60 to 69 years old, and 70 years and older, who were enrolled in a previous study for cross-reactive H3 antibodies.…”
Section: Discussionmentioning
confidence: 99%